Analysis of the Competency of People's Shipping Ship Crews in Determining the Position of the Ship (Case Study: Pelra Ship at Maccini Baji' Harbor, Pangkajene Regency and the Islands and Paotere-Makassar People's Harbor) - Rachman, Subehana; Asri, Haerani; Kendek, Meti; Suriadi, Adi (Dinasti Publisher, 2025)
This research aims to identify Pelra human resources with GT 35-250 Tonnage in navigating, especially determining the position of the ship during shipping and to determine the implementation of regulatory standards related to the competency of Pelra HR with GT 35-250 Tonnage in carrying out manning on board. The data analysis technique used in this research is a quantitative descriptive analysis technique using a reliable questionnaire. This technique uses a percentage of qualitative data that is quantitative to make it easier to obtain final results from two or more variables and then the data is qualitative again. The data analysis technique used is multiple linear analysis with SPSS 26.0 software. Based on the results of the data analysis above, Pelra's resources with GT 35-250 Tonnage in navigating to determine the position of the ship on the voyage, viewed from the results of the data analysis above, show that the human resources of people's shipping in carrying out navigation when determining the position of the ship are said to be good and need to be improved several times. so that human resources can be maximized in navigation when determining the position of the ship, while the implementation of regulatory standards related to the competency of Pelra's HR with GT 35-250 Tonnage in carrying out manning on board, based on research results, is said to be good, but it is still necessary to improve the competency of HR according to regulatory standards in carrying out manning on board the ship in order to reduce risks and dangers when determining the position of the ship. Keywords: ship crew competency, determining the position of the ship, shipping safety